تطبيق طريقة سوروكان في تعليم كتب التراث - Amirul Mukminin; Khoirul Anwar; Aisyatul Hanun (Fakultas Tarbiyah Universitas Ibrahimy, 2021)
This research started from learning at Al-Badriyah Islamic Boarding School which since established applying Sorogan Method in some lesson kitab turats, the students and the graduates proved to have the ability to understand the Qur'an and religious books needed in the community, therefore the graduates of Al-Badriyah Islamic Boarding School have a role in religious field in society, and some graduates have successfully established educational institution, this proves that the study of book in Al-Badriyah Islamic Boarding School done well, one way learn kitab turats in this Islamic Boarding School using the Sorogan Method. This study aims to know and analyze: 1). the implementation of Sorogan Method in Al-Badriyah Islamic Boarding School Sundak Rarang East Lombok. 2). the students ability in reading kitab turats by using Sorogan Method at Al-Badriyah Islamic Boarding School Sundak Rarang East Lombok from 2014 until 2017. This research is a case study research using qualitative research approach, that is research which have characteristic that its data is natural phenomenon and oral information. Data collection techniques use observation, interviews, and documentation. Based on the results of the research can be concluded that: 1). The implementation of the Sorogan method is realized with two ways. (a). One student called to go forward to become readers and mean while other friends listening then explained by teacher, all students get turn to progressing to become a reader and not all students get a turn in a meeting of learning but usually the reader 2 to 3 students because of time limitations, while the student who have not got a turn at the learning meeting will get a turn in the next week. The students read the book in his study in front of the teachers then on the sidelines of the reading student sometimes he was asked by his teacher about how to read nahwu and sharafnya, after then teacher give explanation about the discussion at that time. 2). While the ability of students in reading kitab turats with sorogan method is very good and continue to increase because the student continue to get improvements and additional knowledge in reading the kitab turats, but the number of students who follow lesson in particular lesson kitab turats with sorogan method less.